At the Crossroads:: Saudi Arabia's Dilemmas - Boukhars, Anouar (Journal of Conflict Studies, 2006)
Abstract In the course of the last decade it has become clear that events have gone wrong in Saudi Arabia. A deep intra-societal struggle cuts across all formative institutions of the country and the house of Al Saud is at pains to address its profound crisis of legitimacy and performance, the overwhelming crisis of identity associated with modernity, the internal and external pressures for socio-economic reforms, and the complex and multi-faceted phenomenon of religious extremism. This article examines the formidable challenge of addressing frustrated popular expectations, and reforming the state's religious institutions and rigid politico-ideological agenda without alienating the substantial conservative constituency on which the monarchy's legitimacy depends. It also traces the historical and the ideological roots of international and local jihadism as well as the evolution of Wahhabism from a retrograde but status quo-oriented philosophy into a radical ideology prone to violence and terrorism.